Analisis Pengaruh Rasio Keuangan Terhadap Profitabilitas Pada Bank Umum Syariah Periode 2013-2022 - Natalisa Margaretha (ITB AAS INDONESIA Surakarta, 2023)
Profitability is important to know how much the Sharia Bank contributes to the Indonesian economy. The study aims to analyze the profitability of the Shariah public bank in Indonesia in the period 2013-2022. The research was conducted using a quantitative approach by performing a panel data regression test. The data used in this study are secondary data obtained from the annual reports of the Financial Services Authority and the annual financial reports of each Shariah general bank. Panel data regression results showed that the financing to Deposit Ratio, Non-Performing Finance, Operational burden, and Operational Revenue had a negative and significant impact on the profitability (Return on Assets) of the period 2013–2022, while the Capital Adequacy Ratio had a positive and significant effect on the return on assets of the 2013–2022 period.